Computational Forensic Linguistics: An Overview of Computational Applications in Forensic Contexts - Sousa-Silva, Rui (Language and Law / Linguagem e Direito, 2019)
The number of computational approaches to forensic linguistics has increased significantly over the last decades, as a result not only of increasing computer processing power, but also of the growing interest of computer scientists in natural language processing and in forensic applications. At the same time, forensic linguists faced the need to use computer resources in both their research and their casework – especially when dealing with large volumes of data. This article presents a brief, non-systematic survey of computational linguistics research in forensic contexts. Given the very large body of research conducted over the years, as well as the speed at which new research is regularly published, a systematic survey is virtually impossible. Therefore, this survey focuses on some of the studies that are relevant in the field of computational forensic linguistics. The research cited is discussed in relation to the aims and objectives of the linguistic analysis in forensic contexts, paying particular attention to both their potential and their limitations for forensic applications. The article ends with a discussion of future implications.